ANALISIS PEMBERIAN VARIASI KONSENTRASI MOLASES TERHADAP KUALITAS BIOPELLET ARANG TEMPURUNG KELAPA - Fiba Granza Al Ghifari; Soni Sisbudi Harsono (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2021)
Biopellet is one of the natural fuels that is relatively low price and renewable. Coconut shell waste that is widely or rarely used can be used as one of the main ingredients of biopellet manufacturing. Utilization becomes the main material in the manufacture of biopellet to know the feasibility can be done characteristic tests after the manufacture of biopellet from coconut shell charcoal and will be obtained the best quality. The treatment variable in this study was to provide variation in the adhesive content of molasses. The variations of the molasses adhesive used were with concentrations of 10%, 15%, 20%, and 25%. The analytical method used a one-way ANOVA test with the F test method and the further test is the Tuckey test the results obtained after the conduct of this study obtained the smallest moisture content value in the biopellet dose of 10 % by 1.02 %. The smallest ash content value in biopellet at a dose of 25 % is 6.74 %. The value of the smallest volatile matters content in biopellet at a dose of 10 % is 76.01 %. The largest carbon content value tied to biopellet at a dose of 10 % is 12.58 %. The largest calorific value in biopellet with a dose of 10% was 4783.56 kal/g. The longest fuel consumption rate in biopellet at a dose of 10% was 0.092 g/s. The old value of boiling the fastest water in the biopellet at a dose of 10% is 22,32 minutes. The largest efficiency value in biopellet at a dose of 10% is 20.22 %. Best Composition in this study on adhesive variation 10%.